(untitled) (SENSISTEK:Riset Sains dan Teknologi Kelautan, 2022)
In a construction activity, there are several aspects that require proper management and processing required to have accuracy, determination, performance, accuracy, and safety to produce the appropriate end with expectations. In a project, it is necessary to handle good scheduling management. Because of Therefore, it needs to be handled with careful and thorough calculations so that no mistakes occur when the project is in progress just lasts. The duration of a project does not have to add up the total time of the activity, but enough to find the critical path. Scheduling a project is an outcome factor that can provide information about the schedule plan and progress of the project. In this case, the resource performance is costs, personnel, equipment and materials, and project duration planning. When working on a project, problems often arise, namely the project implementation time does not match the agreed time. Matter This will have a negative impact on the company. As a result, when a project is not well planned, Project implementation involves each other throughout a series of activities that will influence each other.